Analysis of ICT Framework of Junior High School Teachers in Depok City in Supporting In-depth Learning: (Study on Schools Receiving Operational Assistance for School Performance 2025) - Yulaikhah, Siti; Suharyati, Henny (Society : Jurnal Pengabdian Masyarakat, 2025)
This study aims to analyze the readiness of junior high school teachers receiving the 2025 Performance-Based School Operational Assistance (BOS Kinerja) in utilizing Information and Communication Technology (ICT) to support deep learning. A total of 100 teachers from various public and private schools participated in the study. Data were collected using a questionnaire based on the UNESCO ICT Competency Framework for Teachers and analyzed using quantitative descriptive methods. The results indicate that teachers' readiness in the domains of knowledge acquisition (KA) and knowledge deepening (KD) to support deep learning falls into the "ready" category. The highest competency was observed in the knowledge acquisition aspect, with a mean score of4.12, followed by knowledge deepening at 3.75, and knowledge creation (KC) at 3.30, which indicates a "fairly ready" status and highlights the need for further reinforcement. 78.9% of teachers stated that they have integrated ICT into their lesson plans (RPP). However, only 42.2% reported that this integration supports project-based, collaborative, and reflective learningChallenges remain in increasing the consistent use of ICT and optimizing practice-based training. These findings are essential for data-driven, targeted, and sustainable policy-making aimed at enhancing teachers' digital competencies.